Correlation of heat shock protein 1 expression with progression and prognosis of non-small cell lung cancer - Wang, Rui; Guo, Rongqi; Huang, Tianyi; Lu, Yu; Zhang, Weisong; Wang, Yihao; Ni, Qinggan; Song, Jianxiang; Li, Xia (Frontiers in Oncology, 2025)
AimsTo investigate the expression and clinical significance of heat shock protein H1 (HSPH1) in non-small cell lung cancer (NSCLC). To provide new and reliable biomarkers for the treatment of NSCLC.Main methodsVarious public databases were used to analyse the molecular characteristics, disease relevance and expression differences of HSPH1 and to investigate the correlation between HSPH1 expression and prognosis in NSCLC patients. MsigDB and Molecular signatures database were used for enrichment analysis. The HSPH1 protein interaction network was constructed using the STRING database. In addition, immune infiltration analysis was performed. Subsequently, the expression levels of HSPH1 in Lung cancer cell lines, human NSCLC tissues and normal tissues were determined using various experiments. Finally, a retrospective analysis was performed to determine whether the expression level of HSPH1 was associated with the clinical characteristics and prognosis of NSCLC patients.ResultsThe high expression of HSPH1 in NSCLC was significantly correlated with the clinical characteristics and poor prognosis of patients, and it may affect the progression of NSCLC by forming a regulatory network with molecules such as HSPA8, BAG2, etc., and its mechanism may involve the regulation of the P53 signalling pathway, G2M_CHECKPOINT and mTORC1_SGNALING. Experiments confirmed that HSPH1 was also highly expressed in NSCLC tissues and cells.ConclusionHSPH1 can be used as a potential diagnostic and prognostic marker for NSCLC, and its involvement in NSCLC progression and immune regulation may be one of its therapeutic targets.